A constructive method for finding periodic solutions of differential systems - Kenzhebaev, K. K. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
Coefficient conditions for the existence of periodic solutions of degenerate systems of differential equations are obtained. Iterative algorithms for finding these solutions are developed.